MATHEMATICS AND STATISTICS - Amirov Ilyas son of Landing (Web of Journals Publishing, 2025)
Mathematics and statistics are two fundamental disciplines that are relevant for the development of modern society. Their knowledge is used in various fields and will not lose its relevance in the future.
Keywords: Mathematics, Statistics, types, tasks, mathematical statistics, strengthening foundations, fields of application, fields of study.